Microbial profile of digesta in diabetic experimental animals fed with parboiled rice - Azhad, M. Hafiz; Pujimulyani, Dwiyati; Yulianto, Wisnu Adi (JITIPARI, 2026)
Rice is a staple food for nearly two-thirds of the world's population, including Indonesians. Rice generally has a high glycemic index (GI) and cannot be consumed by diabetics.  Pratanak rice has a low GI, so it is recommended for diabetics. The study aimed to evaluate the effect of parboiled rice on the amount of LAB (Lactic Acid Bacteria), pH, and SCFA (Short-Chain Fatty Acids) of diabetic experimental animals. The research method consisted of 6 groups of rats with groups 1 (Cr and Mg fortified parboiled rice), 2 (Cr, Mg and cinnamon fortified parboiled rice), 3 (nonfortified parboiled rice), 4 (ciherang rice), 5 (standard feed for healthy rats), 6 (diabetic rats). All groups of rats were adapted for 3 days with standard feed and treatment for 14 days. LAB, pH, and SCFA were analyzed, statistical tests using One Way Anova if significantly different, followed by DMRT test. Giving chromium, magnesium, and cinnamon fortified rice gave a significant difference in the amount of LAB, pH, and SCFA feces between the treatment group and the control group. Thus, pre-cooked rice fortified with Cr, Mg, and cinnamon has the potential to be a healthier food option for individuals with diabetes.